The Situation of Communication and Media in the Syrian Refugee Camps in Jordan (The Zaatari Camp as a Model) - Olaimat, Farhan; AL-Tahat, Khalaf (Dirasat: Human and Social Sciences, 2022)
This study aims to identify the communication and media reality in the Syrian refugee camps in Jordan. In addition, there are other aims such as knowing the reality of communication among Syrian people in camps through identifying the most used Jordanian, Arab and international means of communications and social media. And the extent to which these means of communications satisfy the requirements of Syrians in camps. This study is considered one of the descriptive studies that was based on the survey method through the questionnaire tool on a sample of 243 participants from the Zaatari refugee camp. The study came up with many results , the most important:: It was found that 95.1 of the study sample owned a smart phone, 39.5 owns a computer, -91.4 owns a TV, and 70.4 owns a Satellite TV receiver,92.2 owns internet packages connected to their smart phones,34.4 owns home internet packages -It was found that the majority of the study sample suffers from problems in the Internet, and The Jordanian Television is the most Jordanian media to be followed. It was also found that WhatsApp is the most used social media by the study sample. Moreover, half of the study sample was found to be dissatisfied with communication services in the camp. Accordingly, this paper provides the following recommendations: It is necessary to improve the internet services in Syrian camps in Jordan. And that Jordanian and Arab means of communication show more care for Syrian refugees and their problems.